2013
DOI: 10.1515/jbcpp-2012-0040
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and their role in hyperthermia and heat stroke

Abstract: Cytokines are intracellular peptides that serve as immune mediators. The levels of both pro- and anti-inflammatory cytokines have been demonstrated to rise in the event of heat stroke in both human and animal models. Different hyperthermic states, including both normal exercise-induced hyperthermia and classical and exertional heat stroke, result in unique characteristic profiles of plasma cytokines. The complexity of the interaction between pro- and anti-inflammatory cytokines is outlined in the vast number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 61 publications
0
65
0
Order By: Relevance
“…During HS, the levels of both pro-inflammatory and anti-inflammatory cytokines increase. This is due to endotoxemia, which is a storm of microbial endotoxin (i.e., LPS-lipopolysaccharides) infiltrating the milieu of the body [56]. In the current study, slow-growing chickens that were subjected to chronic HS demonstrated a significantly higher expression of IL-10 and IL-12p40.…”
Section: Immune-related Gene Expression Signaturesmentioning
confidence: 51%
“…During HS, the levels of both pro-inflammatory and anti-inflammatory cytokines increase. This is due to endotoxemia, which is a storm of microbial endotoxin (i.e., LPS-lipopolysaccharides) infiltrating the milieu of the body [56]. In the current study, slow-growing chickens that were subjected to chronic HS demonstrated a significantly higher expression of IL-10 and IL-12p40.…”
Section: Immune-related Gene Expression Signaturesmentioning
confidence: 51%
“…Heatstroke manifests as hyperthermia, tachypnea, panting, collapse, 61 shock, altered consciousness, seizures, vomiting, diarrhea, petechiae and ecchymosis (Bruchim 62 et al, 2006) parenchymal injury (Langston, 2010). The pathogenesis of heatstroke-associated AKI is most 70 likely multifactorial, and includes decreased perfusion due to dehydration and hypovolemia, 71 direct thermal injury, rhabdomyolysis-associated myoglobinuria and SIRS (Heled et al, 2013). 72…”
Section: Introduction 56mentioning
confidence: 99%
“…8 The mechanism underlying multiple organ dysfunction syndrome of heatstroke is not fully understood, but direct thermal injury to the endothelium, activation of the inflammatory and coagulatory pathways, tissue ischaemia and/or endotoxemia and cytokines have been suggested. 9,10 The key measures to maximise the survival chances of heatstroke patients are as follows: rapidly decreasing the elevated core body temperature and organ support of central nervous system, cardiovascular, pulmonary, renal system and the management of late or post-cooling complications. 1113 After admission, our patient presented with acute renal injury, acute hepatic failure, skeletal muscle damage and disseminated intravascular coagulation soon.…”
Section: Discussionmentioning
confidence: 99%